Analisis Google Trends: Akulturasi budaya melalui musik Kpop di Indonesia - Betty Masruroh; Ifan Deffinika; Vira Setia Ningrum; Prananda Anugrah; Fuad Maysa (Universitas Negeri Malang, 2023)
Culture is the result of human taste, initiative and creativity that grows and develops in a certain environment and region. The current digital era makes it easy to spread information to various countries in the world. Information that is spread does not escape from cultural content. This causes cultural acculturation, one of which is in the arts area. This research aims to find people's interest in Korean music through the two groups based on Google trends data. Understanding the interests of internet users through Google Trends will increase insight into the popularity and influence of Korean culture in Indonesia to provide insight for people interested in cultural acculturation and the development of K-pop music. This study uses a qualitative research method with a netnographic approach with data sources from Google Trends. The data is presented in the form of a description of the results of observations and interviews after being reduced first. The results showed that Korean bands were one of the factors that brought cultural acculturation to Indonesia. The Korean wave trend has both positive and negative impacts which can be a challenge for Indonesia in the future. Budaya merupakan hasil dari rasa, karsa, dan cipta manusia yang tumbuh dan berkembang dalam lingkungan dan wilayah tertentu. Era digital saat ini memudahkan penyebaran informasi ke berbagai negara di belahan dunia. Informasi yang tersebar tak luput dari muatan budaya. Hal ini menyebabkan adanya akulturasi budaya, salah satunya pada wilayah kesenian. Penelitian ini bertujuan untuk mengetahui minat masyarakat terhadap musik Korea melalui kedua grup tersebut berdasarkan data tren Google. Pemahaman terhadap minat pengguna internet melalui Google Trends ini akan meningkatkan wawasan tentang popularitas dan pengaruh budaya Korea di Indonesia sehingga dapat memberikan wawasan bagi masyarakat yang tertarik dengan akulturasi budaya dan perkembangan musik Kpop. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan netnografi dengan sumber data dari Google Trendss. Data disajikan dalam bentuk deskripsi dari hasil pengamatan dan wawancara setelah direduksi terlebih dahulu. Hasil penelitian menunjukkan bahwa Band Korea merupakan salah satu faktor pembawa akulturasi budaya ke Indonesia. Tren gelombang Korea ini memiliki dampak positif dan negatif yang dapat menjadi tantangan bagi Indonesia kedepannya.